CCAAT/enhancer-binding protein β promotes receptor activator of nuclear factor-kappa-B ligand (RANKL) expression and osteoclast formation in the synovium in rheumatoid arthritis - Tsushima, Hidetoshi (Arthritis Res Ther, 2015)
INTRODUCTION: CCAAT/enhancer-binding protein β (C/EBPβ) is a transcription factor that is activated in the synovium in rheumatoid arthritis (RA) and promotes expression of various matrix metalloproteinases. In this study, we examined whether C/EBPβ mediates the expression of receptor activator of nuclear factor-kappa-B ligand (RANKL) and drives osteoclast formation in primary fibroblast-like synoviocytes (FLS) from RA patients. The cooperation of C/EBPβ and activation transcription factor-4 (ATF4) in the regulation of the RANKL promoter was also investigated. METHODS: Immunofluorescence staining was performed for C/EBPβ, RANKL, and ATF4 in synovium from RA patients. Adenovirus expression vectors for two major isoforms, C/EBPβ-liver-enriched activator protein (LAP) and - liver-enriched inhibitory protein (LIP), or small interfering RNA for C/EBPβ, were used to manipulate C/EBPβ expression in RA-FLS. RA-FLS over-expressing C/EBPβ were co-cultured with peripheral blood mononuclear cells (PBMCs) to test osteoclast formation by tartrate-resistant acid phosphatase (TRAP) staining. A promoter assay for RANKL, a chromatin immunoprecipitation (ChIP) assay and an immunoprecipitation (IP) assay were also performed. RESULTS: Immunofluorescence staining showed colocalization of C/EBPβ, ATF4 and RANKL in RA synovium. Western blotting revealed the expression of C/EBPβ-LAP and -LIP in RA-FLS. Over-expression of either C/EBPβ-LAP or -LIP significantly increased the expression of RANKL mRNA, while C/EBPβ-LIP down-regulated osteoprotegerin (OPG) mRNA. The RANKL/OPG mRNA ratio was significantly increased by C/EBPβ-LIP over-expression. Knockdown of C/EBPβ with siRNA decreased the expression of RANKL mRNA. The number of TRAP-positive multinucleated cells was increased in co-cultures of PBMCs and FLS over-expressing either C/EBPβ-LAP or -LIP, but was more significant with LIP. C/EBPβ-LIP does not have a transactivation domain. However, promoter assays showed that C/EBPβ-LIP and ATF4 synergistically transactivate the RANKL promoter. ChIP and IP assays revealed the cooperative binding of C/EBPβ and ATF4 on the RANKL promoter. CONCLUSIONS: We demonstrated that C/EBPβ, especially C/EBPβ-LIP in cooperation with ATF4, is involved in osteoclast formation by regulating RANKL expression in RA-FLS. These findings suggest that C/EBPβ plays a crucial role in bone destruction in RA joints. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13075-015-0532-6) contains supplementary material, which is available to authorized users.